Optimal Ovulation Trigger–Oocyte Pickup Interval in Progestin-Primed Ovarian Stimulation Protocol: A Retrospective Study Using Propensity Score Matching - Shen, Xi; Long, Hui; Guo, Wenya; Gao, Hongyuan; Cai, Renfei; Jin, Wei; Yan, Zhiguang; Zhang, Shaozhen; Wang, Yun; Lyu, Qifeng; Wang, Li; Kuang, Yanping (Frontiers in Endocrinology, 2019)
Background: To investigate the optimal ovulation trigger–oocyte pickup (OPU) interval of a progestin-primed ovarian stimulation (PPOS) protocol. Method: Patients with normal ovarian reserve in their first PPOS OPU cycle were enrolled in this retrospective cohort study between July 2013 and April 2018. This retrospective cohort study included two parts. In part I, we studied the regression trend of mature oocyte rate, implantation rate, and live birth rate within the whole ovulation trigger–OPU interval of 7,258 patients. To homogenize some clinical characters that were key regulators of OPU time, in part II, we used propensity score matching to auto-select patients among trigger–OPU interval group 1 (35.6–36.4 h), group 2 (36.4–37.1 h), and group 3 (37.1–37.8 h) and analyzed clinical outcomes. Results: Study part I showed that the whole ovulation trigger–OPU interval (33–39.5 h) of PPOS protocol had a trend of a high mature oocyte rate (>80%), increasing implantation rate, and high live birth rate. Propensity score matching of patients with homogeneous clinical characteristics further indicated that the trigger–OPU interval within groups 2 and 3 (36.4–37.8 h) had significantly higher mature oocyte rates (84.54% vs. 84.60% vs. 82.34%, P = 0.002) and implantation rates (34.17% vs. 34.37% vs. 29.61%, P < 0.05) than group 1. The same tend was observed in the live birth rate. Conclusions: The ovulation trigger–OPU interval of 36.4–37.8 h is optimal for most patients using a PPOS protocol.